Three-component Synthesis of 4-Arylidene-3-alkylisoxazol-5(4H)-ones in the Presence of Potassium 2,5-dioxoimidazolidin-1-ide - Reihani, Neda; Kiyani, Hamzeh (Current Organic Chemistry, 2021)
An efficient synthesis of 4-arylidene-3-alkylisoxazole-5(4H)-ones has been implemented via the three-component cyclocondensation of aryl(heteroaryl)aldehydes with hydroxylamine hydrochloride and β-ketoesters. The potassium 2,5-dioxoimidazolidin-1-ide has been introduced as the new organocatalyst to facilitate this heterocyclization. In the current process, three starting materials, including substituted benzaldehydes/heterocyclic aromatic aldehydes, hydroxylamine hydrochloride, and ethyl acetoacetate/propyl acetoacetate/butyryl acetoacetate have been successfully used to synthesize the number of substituted isoxazole- 5(4H)-ones in good to high yields in ethylene glycol as a green reaction medium at 80 ºC. The low catalyst loading is also a main advantage over some reported catalysts.
Keywords: 5-dioxoimidazolidin-1-ide